DETERMINING THE OPINIONS AND SATISFACTION OF NURSING STUDENTS WHO SWITCHED TO ONLINE EDUCATION SYSTEM DURING THE COVID-19 PANDEMIC - YÜCEL, Adalet; KÜÇÜKOĞLU, Sibel; TAŞ ARSLAN, Fatma (Göbeklitepe Medical Science Journal, 2022)
The aim of this study is to determine the opinions and satisfaction of the nursing students who suddenly switched from face-to-face education to the online education system, in the early period of the Covid-19 pandemic. The research was carried out with a nursing student (n=475) studying at two state and one private universities in Konya between June-August 2020. "Introductory Information Form", "Satisfaction Scale Regarding the e-Learning Process" and "Opinions Regarding Distance Education Scale" were used to collect the research data. Ethical principles were adhered. It was determined that the satisfaction levels of the students with e-Learning Process (81.17±26.08) and Scores of the Opinion Scale towards Distance Education (55.32±10.53) were close to the middle level. It was determined that the mean score of both scales was affected by the class of education, the type of university and the possibility of following the distance education system (p<0.05). The first three problems of the students about the online education system; "Experiencing technical problems during lessons" (74.5%), "understanding the lessons adequately due to lack of clinical practice" (71.2%) and "difficulty concentrating" (68.6%). It is recommended that the study be repeated with nursing students who continue online education in the later stages of the pandemic.